Low‐frequency mechanical vibration induces apoptosis of A431 epidermoid carcinoma cells - Anggayasti, Wresti L. (Eng Life Sci, 2020)
Cancer research is increasingly focused on discovering strategies to induce cancer cell apoptosis without affecting surrounding normal cells. One potential biocompatible method is mechanical vibration, which has been developed as part of the emerging field of mechanomedicine. Previous studies of mechanical vibration have employed high‐frequency vibration, which damages healthy cells. In this study, we examined the effects of brief (1 h) low‐frequency (20 Hz) mechanical vibration on glucose consumption and survival (apoptosis, necrosis, HMGB1 release) of the human epidermoid carcinoma cell line A431. We found that apoptosis, but not necrosis, was significantly increased at 48 h after mechanical vibration compared with cells maintained in static culture. In keeping with this, extracellular release of HMGB1, a necrosis marker, was lower in cultures of A431 cells subjected to mechanical vibration compared with control cells. Glucose consumption was increased in the first 24 h after mechanical vibration but returned to control levels before the onset of apoptosis. Although the precise intracellular mechanisms by which low‐frequency mechanical vibration triggers apoptosis of A431 cells is unknown, these results suggest a possible role for metabolic pathways. Mechanical vibration may thus represent a novel application of mechanomedicine to cancer therapy.